AGRONOMIC CHARACTERS OF WHEAT (TRITICUM AESTIVUM L.) GROWN USING TWO CROPPING SYSTEMS IN MEDIUM LAND OF PALOPO CITY - Mayasari Yamin; Sartia Hama; Taufiq Hidayat (Universitas Sembilanbelas November Kolaka, 2018)
Wheat (Triticum aestivum L.) is a staple food for most of world population and has a good prospect considering the great potential of land to be planted with this plant species which contains carbohydrate of 70% and protein of 3%. The development of this commodity was started from agricultural extensification and production increase through the implementation of cropping system. This study was aimed to provide information on suitable cropping system for wheat cultivation and to examine the effect of cropping system on the increase in wheat production in medium land of Palopo City. This study was conducted in farmer land in Kambo Village, Mungkajang Subdistrict of Palopo City, South Sulawesi at elevation of ± 600 m asl from June until September 2017. This research uses two factor factorial in randomized block design. The first factor consisted of two cropping systems, namely line up system (S1) and Hazton system (S2). While, the second factor included two varieties, namely Guri 4 variety (V1) and Guri 6 variety (V2). Study result for vegetative phase showed that the best plant height was obtained using line up cropping system in Guri 4 variety (S1V1) with average of 73.91 cm. Implementation of Hazton cropping system in Guri 4 variety (S2V1) resulted in the best flag leaf area with average of 40.23 cm2. Hazton cropping system implementation in Guri 6 variety (V2S2) indicated the best green color with average value of 11.00 unit. Furthermore, application of line up cropping system (S1) produced the best total tiller number with average of 18.22 tillers. Therefore, it is concluded that the use of Hazton cropping system was able to increase the wheat production and Guri 4 Variety is expected to adapt to grow in the medium land of Palopo City